EFFECTIVENESS OF PROVIDING DIRECT VISUALIZATION ABOUT THE DANGERS OF CIGARETTES TO THE LUNGS ON THE KNOWLEDGE AND ATTITUDES OF STUDENTS OF SMAN 1 KANDAT - Octavi Hemi, Chrisita; Ukik Agustina; Predito Prihantoro (Universitas STRADA Indonesia, 2026)
Cigarettes are a major cause of health problems, particularly serious lung disease. Smoking habits among adolescents are increasing and can pose long-term health risks. Effective education about the dangers of smoking is crucial from an early age. The use of direct visualization media is believed to improve students' understanding and awareness better than conventional methods. This study aims to analyze the effectiveness of direct visualization about the dangers of smoking on the lungs in improving the knowledge and attitudes of students at SMAN 1 Kandat. This research was pre-experimental study with one-group pretest-posttest design. The research samples were 95 eleventh-grade students. The Samples were chosen with accidental technique sampling that selected based on discussions conducted by all examiners and guidance counselors at SMAN 1 Kandat. The main instrument was a valid and reliable questionnaire to measure knowledge and attitudes before and after visualization intervention with simulation. The study showed a significant increase in knowledge, from the “poor” category (86.3%) before the intervention to “good” (88.4%) after the intervention. Attitudes also shifted from predominantly negative (76.8%) to more positive (89.5%) after the intervention. The Wilcoxon Signed Ranks Test showed a significant difference in knowledge and attitudes before and after the intervention (p < 0.05), so there was a difference in knowledge and attitudes before and after direct visualization. This study found that the use of direct visualization as